The more, the better? A multivariate longitudinal study on L2 motivation and anxiety in EFL oral presentations - Wu, Hao (Frontiers in Education, 2024)
For decades, oral presentations have become a common method of assessment in language learning classrooms. Nonetheless, anxiety is a persistent negative feeling pervasive in EFL learners. Although applied linguistic research suggests that there is a relationship between motivation and anxiety, the nature and direction of this relationship remain inconsistent. To tackle this concern, this mixed-methods longitudinal study aimed to investigate the growth trajectories of Chinese EFL learners’ L2 motivation and anxiety in oral presentations. The participants were 171 second-year undergraduate medical students who attended an English for Academic Purposes (EAP) course. They delivered four oral presentations and reported their L2 motivation and anxiety levels in questionnaire surveys. Results show that: (1) As the number of EFL learners giving oral presentations increased, the L2 motivation levels increased, and the anxiety levels decreased. (2) Those who were initially more anxious about giving oral presentations had higher decrease rates during the four oral presentations. (3) There was co-development but inverse relationships between ideal L2 self and anxiety and between ought-to L2 self and anxiety, although a complete parallel process model was not established. These findings suggest that students’ perceptions of L2 motivation interact with anxiety levels over time but in a sophisticated fashion. Finally, pedagogical implications for EFL oral presentation instruction are provided.